A new genus and species of the subfamily Laphyragoginae (Hymenoptera, Apoidea, Crabronidae) with analysis of the relationship of Eremiaspheciinae and Laphyragoginae, stat. resurr. - Mokrousov, Mikhail V.; Proshchalykin, Maxim Yu. (Zootaxa, 2025)
Based on remarkable morphological differences between the two species groups of Laphyragogus Kohl, 1889, the genus is split into Laphyragogus and a new genus, Asphaleia Mokrousov, gen. nov. (type species A. gussakovskii Mokrousov, sp. nov.). Three species are transferred from Laphyragogus to the new genus: Asphaleia ajjer (de Beaumont, 1958), comb. nov., A. gessae (Schmid-Egger, 2022), comb. nov. and A. orientalis (de Beaumont, 1970), comb. nov. Based on morphological analysis, it is shown that Eremiaspheciini and Laphyragogini are not closely related and the status of Laphyragoginae as its own subfamily is resurrected.